Exploring the antiviral potential of shikimic acid against Chikungunya virus through network pharmacology, molecular docking, and in vitro experiments - Xin, Jialiang; Song, Xingxing; Zheng, Haohong; Li, Wenjing; Qin, Yuyang; Wang, Wei; Zhang, He; Peng, Guangneng (Frontiers in Veterinary Science, 2025)
Chikungunya virus (CHIKV) is an arbovirus that can lead to chronic arthritis and significantly diminish the quality of life of patients. Given the expanding global prevalence of CHIKV and the absence of specific antiviral therapies, there is an urgent need to explore effective treatment options. This study aimed to evaluate the antiviral effects of shikimic acid (SA) against CHIKV through a combination of network pharmacology, molecular docking, and in vitro assays. Network pharmacology analysis identified 26 potential targets through which SA could inhibit CHIKV, including key pathogenic targets such as TNF, IL-6, and MAPK3. This hypothesis was further supported by molecular docking. The molecular docking analysis revealed that SA could interact with multiple CHIKV-related targets, including EGF, with vina scores generally lower than −6, indicating a high propensity for stable complex formation. The results also suggested that SA could potentially disrupt the IL-17 signaling pathway by engaging with various targets to form complexes. In vitro experiments confirmed that SA significantly enhanced the viability of 293T and BHK-21 cells infected with CHIKV by ~25% and reduced viral load by over 20% at concentrations ranging from 1,000 to 31.25 μM. Additionally, SA was found to markedly downregulate the expression of CHIKV-related attachment factors ACTG1, TSPAN9, and TIM-1 in 293T cells infected with CHIKV. Furthermore, RT-qPCR analysis demonstrated that SA effectively decreased the expression of NFKB1, PTGS2, RELA, and EGF related to the IL-17 signaling pathway. In conclusion, these findings indicate that SA is a promising candidate for developing treatment strategies targeting CHIKV with good clinical application value.